Cocaine intake correlates with risk-taking behavior and affects estrous cycling in female Sprague–Dawley rats - Truckenbrod, Leah M.; Cooper, Emily M.; Wheeler, Alexa-Rae; Orsini, Caitlin A. (Frontiers in Behavioral Neuroscience, 2023)
Navigating complex decisions and considering their relative risks and rewards is an important cognitive ability necessary for survival. However, use of and dependence on illicit drugs can result in long-lasting changes to this risk/reward calculus in individuals with substance use disorder. Recent work has shown that chronic exposure to cocaine causes long-lasting increases in risk taking in male and female rats, but there are still significant gaps in our understanding of the relationship between cocaine use and changes in risk taking. For example, it is unclear whether the magnitude of cocaine intake dictates the extent to which risk taking is altered. To address this, male and female Sprague-Dawley rats underwent cocaine (or sucrose) self-administration and, following a period of abstinence, were trained and tested in a rodent model of risky decision making. In this behavioral task, rats made discrete-trial choices between a lever associated with a small food reward (i.e., “safe” option) and a lever associated with a larger food reward accompanied by a variable risk of footshock delivery (i.e., “risky” option). Surprisingly, and in contrast to prior work in Long-Evans rats, there were no effects of cocaine self-administration on choice of the large, risky reward (i.e., risk taking) during abstinence in males or females. There was, however, a significant relationship between cocaine intake and risk taking in female rats, with greater intake associated with greater preference for the large, risky reward. Relative to their sucrose counterparts, female rats in the cocaine group also exhibited irregular estrous cycles, characterized by prolonged estrus and/or diestrus phases. Collectively, these data suggest that there may be strain differences in the effects of cocaine on risk taking and highlight the impact that chronic cocaine exposure has on hormonal cyclicity in females. Future work will focus on understanding the neural mechanisms underlying cocaine’s intake-dependent effects on risk taking in females, and whether this is directly related to cocaine-induced alterations in neuroendocrine function.